Radiation efficiency of unbaffled and perforated plates near a rigid reflecting surface - Putra, Azma (Elsevier, 2011)
The accurate prediction of sound radiation from plate-like structures remains a challenging problem. Although the case of a plate set in a rigid baffle can be solved analytically, when the plate radiates sound into free space the problem is more difficult to solve; nevertheless, several approaches have been proposed to determine the sound radiation from an unbaffled plate. The present study extends the consideration to the situation of an unbaffled plate which is located close to a rigid reflecting surface. For this purpose, Laulagnet’s model for the radiation efficiency of an unbaffled plate is extended by modifying the Green’s function to include an image source due to the reflecting surface. The results show that, depending on the distance between the plate and the rigid surface, the radiation efficiency is considerably reduced at low frequencies. Additional reduction of sound radiation can be achieved by introducing perforation to the plate. However, at higher frequencies, the radiation efficiency is amplified relative to that for the plate in the absence of the rigid surface, both with and without perforation. These results have also been validated experimentally.